SCIENTIFIC RATIONALE FOR PRODUCING FERMENTED ICE CREAM WITH PREBIOTIC COMPONENTS - Akhmedova V.R.; Ryabtseva S.A.; Shpak M.A.; Anisimov G.S.; Marugina E.V (Техника и технология пищевых производств)
A new technique for producing fermented ice cream with functional properties was developed, the solution being partial replacement of sucrose for lactulose and a stabilizer - for inulin. The obtained data showed that to improve organoleptic and microbiological characteristics of fermented ice-cream technology lactulose and inulin have to be used for the survival of LAT CW L mesophilic lactococcus. Regularities in the changes of ice cream mixture properties in fermenting with different kinds of starter culture are determined. The choice of the BK-Uglich-AV ( L. acidophilus ) starter culture is substantiated, which allows to carry out ice-cream mixture fermentation up to the titratable acidity of 70-90 °T during 4-6 hours, with the number of starter living cells reaching 10 CFU/g that is necessary for providing standardized microbial attributes of fermented ice cream, in order to provide fermented ice cream mixtures with high antioxidant activity and good organoleptic properties. Regularities in the influence of the sucrose weight fraction on the starter culture development in ice-cream mixtures were determined. The influence of lactulose and inulin on the process of production and quality characteristics of fermented ice cream produced by L. acidophilus was studied. Mathematical relationship fit to the influence of lactulose on the survival of the lactic microorganisms of L. acidophilus during long term storage of the fermented ice cream was obtained. It was found that the addition of 2% inulin had a positive effect on the overrun and melting resistance of the ice cream. The combined use of inulin and lactulose in the fermented ice cream technology can improve the texture and taste, as well as increase the ferment microflora survival rate during storage and extend shelf life of the ice cream.